Study of potentialities of usrp-sdr based radar systems - Tan, Li Qi (2015)
This report describes an exploration study about using Software-Defined Radio (SDR) for low cost SDR based radar applications. The scope of the project includes implementation of radar transmitter, radar receiver, experimental trial and signal processing for target detection. This project will proceed on to wireless communication between two USRP and elaborate more about the set up configuration using GNU Radio programming platform. It extends to the understanding of GNU Radio software which is a programming platform for users to explore the potentialities of radar system. MATLAB algorithm used will also be explained where signal processing is concerned. Multiple applications using Universal Software Radio Peripheral (USRP) will also be experimented and verified.